METAL BIOAVAILABILITY AND DISTRIBUTION IN THE FISH COMMUNITY IN A TROPICAL ESTUARY, SEPETIBA BAY, RIO DE JANEIRO, BRAZIL. - Kütter, Vinicius Tavares; Almeida Moreira, Vanessa; Tavares Kütter, Mateus; Vieira Silva-Filho, Emmanoel; Duarte Marques, Eduardo; Garnier, Jeremie; Dausacker Bidone , Edison (Geochimica Brasiliensis, 2021)
Sepetiba Bay has a wealth of fish species (total 148) as well as a vast area of mangroves and numerous rocky islands, which are important sites of reproduction for marine life. The peculiar environment of the Brazilian coast contains one of the most important industrial centres of south-eastern Brazil. This site has been impacted for decades by the release of industrial (other) emissions and effluents with high metal loads by the steel industry. The ranges of metal concentrations in fish muscle from the species Micropogonias furnieri, Genidens genidens, Cathorops spixii, Notarius grandicassis, Diapterus rhombeus, Selene vomer, Prionotus punctatus, Citharichthys spilopterus, Achirus lineatus, Trinectes paulistanus, Symphurus tessellatus and Hypanus guttatus were measured (Al: 0.02-555.9 µg g-1 d.w., As: 0.0002-20.1 µg g-1 d.w., Cd: <0.0002-0.2 µg g-1 d.w., Cu: 0.2-2.3 µg g-1 d.w., Fe: <0.02-244.9 µg g-1 d.w., Zn: 0.5-227.3 µg g-1 d.w. and Pb: <0.001-1.3 µg g-1 d.w.). The Kruskal-Wallis test revealed significant differences (p<0.05) in the As, Cu, Fe, Pb and Zn contents among fish species. The monitoring of suspended particulate matter during dredging operation revealed the mean metal values for Al (6059±6268 µg g-1), Cd (0.2±0.5 µg g-1), Cu (29±29 µg g-1), Zn (332±892 µg g-1), and Pb (52±70 µg g-1). The accumulation factors of the metal biosediments from the bioavailable sediment fractions and suspended particulate matter showed lower values than those in fish muscle. Arsenic was found at levels above the maximum limit for human consumption according to Brazilian legislation. However, the estimated probability and risk of metal intake via fish consumption showed that the consumption of all species presented low risk.